Evaluation of the Thermal Inactivation of a Salmonella Serotype Oranienburg Strain During Cocoa Roasting at Conditions Relevant to the Fine Chocolate Industry - Yan, Runan; Pinto, Gabriella; Taylor-Roseman, Rebecca; Cogan, Karen; D’Alesandre, Greg; Kovac, Jasna (Frontiers in Microbiology, 2021)
Cocoa roasting produces and enhances the distinct flavor of chocolate, and acts as a critical control point for inactivation of foodborne pathogens in chocolate production. In this study, the inactivation kinetics of Salmonella was assessed on whole cocoa beans using roasting protocols relevant to the fine chocolate industry. Beans were inoculated with 107 -108 log10 CFU/bean of Salmonella enterica subsp. enterica serotype Oranienburg and roasted at 100-150°C for 2-100 min. A greater than 5 log10 reduction of S. Oranienburg was experimentally achieved after 10-min roasting at 150°C. Data were fitted using log-linear and Weibull models. The log-linear models indicated that the roasting times needed to achieve a decimal reduction of Salmonella at 100, 110, 115, 120, 130 and 140°C were 31.98, 17.64, 12.76, 10.49, 4.17 and 1.93 min, respectively. A Weibull model indicated a decrease in the Salmonella inactivation rate over time (β < 1). Statistical analysis indicated that the Weibull model was a better fit compared to a log-linear model. These data demonstrate the efficacy of cocoa roasting in inactivation of Salmonella and may be used to guide food safety decision-making.